Rekonstruksi Pembelajaran PAI di Era Society 5.0 melalui Pendekatan Deep Learning - Ridho Riyanto (ALSYS, 2026)
The pedagogical crisis in Islamic Religious Education (PAI), which remains dominated by memorization and doctrinal transmission models, has created a gap between normative Islamic teachings and the realities of students’ lives in the Society 5.0 era. This study aims to reconstruct PAI learning through a deep learning approach that integrates cognitive, affective, and spiritual dimensions. This study employed library research using a descriptive qualitative approach. The data were drawn from reputable journal articles, academic books, and recent scholarly documents and were analyzed using content analysis and thematic analysis. The findings indicate that the deep learning approach has strong epistemological compatibility with the Islamic traditions of tafaqquh fi al-din, ijtihad, and tadabbur. This conceptual synthesis produced the Deep-Islamic Learning (DIL) model, which comprises four core components: Authentic Islamic Inquiry, Collaborative Meaning-Making, Spiritual-Reflective Praxis, and Transformative Action. This model offers a transformative pedagogical framework that not only deepens religious understanding but also develops reflective religious character oriented toward social impact. The novelty of this study lies in integrating spiritual-reflective dimensions and transcendental action as core components that have not been accommodated in generic deep learning models. Theoretically, this study expands the discourse on critical Islamic pedagogy, while practically, it provides a conceptual framework for teachers and policymakers to transform PAI learning so that it becomes more liberating, enlightening, and relevant to the disruptive digital landscape.